2023
DOI: 10.1021/acs.inorgchem.3c00326
|View full text |Cite
|
Sign up to set email alerts
|

LVVO-Ethyl Maltol-Based Metallodrugs (L2– = Tridentate ONO Ligands): Hydrophobicity, Hydrolytic Stability, and Cytotoxicity via ROS-Mediated Apoptosis

Abstract: Four new oxidovanadium [VVOL1–4(ema)] complexes (1–4) have been synthesized using tridentate binegative ONO donor ligands H2L1–4 [H2L1: (E)-N′-(2-hydroxybenzylidene)furan-2-carbohydrazide; H2L2: (E)-N′-(4-(diethylamino)-2-hydroxybenzylidene)thiophene-2-carbohydrazide; H2L3: (E)-2-(4-(diethylamino)-2-hydroxybenzylideneamino)-4-methylphenol; H2L4: (E)-2-(3-ethoxy-2-hydroxybenzylideneamino)-4-methylphenol] and ethyl maltol (Hema) as a bidentate uninegative coligand and characterized by CHNS analysis, IR, UV–vis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…Dual AO/EB fluorescence staining is an important technique to distinguish normal cells from early and late apoptotic and necrotic cells. AO dye can pass through intact cell membranes and exhibit green fluorescence, whereas EB only stains cells that have lost the integrity of their membranes and exhibit red fluorescence . As shown in Figure , the living cells (control) are seen as green, whereas the apoptotic cells (compound treated) displayed red fluorescence.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Dual AO/EB fluorescence staining is an important technique to distinguish normal cells from early and late apoptotic and necrotic cells. AO dye can pass through intact cell membranes and exhibit green fluorescence, whereas EB only stains cells that have lost the integrity of their membranes and exhibit red fluorescence . As shown in Figure , the living cells (control) are seen as green, whereas the apoptotic cells (compound treated) displayed red fluorescence.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, it is reported that anticancer activity increases with an increase in hydrophobicity. ,, As shown in Table S7, complexes with a high degree of hydrophobicity with log P ow values ranging from 0.643 to 0.588 for 1 – 3 have enhanced anticancer potentials as they facilitate improved cellular membrane crossing by making improved accessibility of compounds in its target. ,,, Also, the order of hydrophobicity correlates with a steady increase in the cytotoxicity against both cancer cell lines. In fact, 1 with a maximum log P ow value of 0.643 ± 0.01 exhibited maximum cytotoxicity results .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations